2013
DOI: 10.1002/jtr.1951
|View full text |Cite
|
Sign up to set email alerts
|

Residents' Perceptions of Tourism Impacts on Island Destinations: A Comparative Analysis

Abstract: This paper presents a comparative analysis of the resident's perception of tourisms impacts on two very successful major mature island destinations (Tenerife and Mallorca). To do so, we conducted a study based on the social exchange theory by using a scale that measures residents' perceptions of tourism's positive and negative impacts on the economy, culture, society and the environment. The results based on more than 1100 interviews show that similar opinions arise on both islands; however, significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 57 publications
2
26
0
6
Order By: Relevance
“…Also, some Yakushima residents fear that the rivers are being polluted by deer carcasses. Hence, tourism not properly managed results in damage to the natural environment and wildlife, pollution to rivers and loss of natural landscape among others effects [62][63][64][65]. Compared to this wide array of issues, discussion in the media and by administrative authorities on Yakushima very narrowly focuses on trampling and human waste in mountain areas.…”
Section: Discussionmentioning
confidence: 99%
“…Also, some Yakushima residents fear that the rivers are being polluted by deer carcasses. Hence, tourism not properly managed results in damage to the natural environment and wildlife, pollution to rivers and loss of natural landscape among others effects [62][63][64][65]. Compared to this wide array of issues, discussion in the media and by administrative authorities on Yakushima very narrowly focuses on trampling and human waste in mountain areas.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have confirmed the social exchange theory (SET), which states that residents perform a cost-benefit analysis and support or reject tourism development depending on the outcome [70]. Thus, a host community will tend to have groups that benefit largely from tourism (for example, people working in the tourism sector) and therefore, tend to support it and downplay its negative impacts, but also groups that see little or few benefits from tourism and underline its negative social and environmental consequences [71].…”
Section: Literature Overview: Islands Tourism and Sustainable Develmentioning
confidence: 99%
“…The use of the term "residents' perceptions" is widespread in the literature (Ap, 1992;Byrd, Bosley, and Dronberger, 2009;Vareiro, Remoaldo, and Cadima Ribeiro, 2013;Garau-Vadell, Díaz-Armas, and Gutierrez-Taño, 2014), although other authors use the expressions "attitudes" (Andereck and Vogt, 2000;Ribeiro, Valle, and Silva, 2013;García, Vázquez, and Macías, 2015;Davis, Allen, and Cosenza, 1988;Williams and Lawson, 2001) or "reactions" (Jurowski, Uysal, and Williams, 1997;Fredline and Faulkner, 2000). Regardless of the use of all types of terms and their semasiology, what most studies show is that residents are reassessed according to their role in direct, indirect, undetermined or induced impacts of tourism in a particular territory.…”
Section: Introductionmentioning
confidence: 99%